Identification of Sleep Patterns via Clustering of Hypnodensities - Mirth, Joshua R.; Felton, Christopher L.; Haider, Clifton R.; McCarter, Stuart J.; Morgenthaler, Timothy I.; Louis, Erik K. St; Holmes, David R. (2023 45th Annual International Conference of the IEEE Engineering in Medicine & Biology Society (EMBC), 2023)
Sleep patterns vary widely between individuals. We explore methods for identifying populations exhibiting similar sleep patterns in an automated fashion using polysomnography data. Our novel approach applies unsupervised machine learning algorithms to hypnodensities graphs generated by a pre-trained neural network. In a population of 100 subjects we identify two stable clusters whose characteristics we visualize graphically and through estimates of total sleep time. We also find that the hypnodensity representation of the sleep stages produces more robust clustering results than the same methods applied to traditional hypnograms.